Management of mandibular flat ridge edentulous using suction denture and neutral zone impression : Penatalaksanaan flat ridge edentulus rahang bawah menggunakan gigi tiruan suction dan pencetakan zona netral - Daniel, Susi; Jubhari, Eri Hendra; Mude, Acing Habibie (Makassar Dental Journal, 2025)
Tooth loss and the use of ill-fitting dentures can cause alveolar bone resorption especially in the mandible. This condition compli-cates the fabrication of a removable denture. Suction denture (SD) is an alternative to improve retention and stable support so that the denture can be used for chewing and swallowing. This article discusses the management of flat ridge condition using SD. A 70-year-old woman came to RSGM Hasanuddin University Makassar complaining of difficulty chewing due to the loss of all her teeth. The treatment chosen was SD with neutral zone impression on the lower jaw. It was concluded that SD can cli-nically improve retention and satisfaction, especially in patients with large alveolar bone resorption.